2023
DOI: 10.1136/bmjopen-2022-064532
|View full text |Cite
|
Sign up to set email alerts
|

Regional disparities in hospital utilisation in Indonesia: a cross-sectional analysis data from the 2018 Indonesian Basic Health Survey

Abstract: ObjectivesPolicymakers must ensure that the entire population has equal access to health services, and efforts to minimise inequalities are needed. This study aimed to analyse the regional disparities in hospital utilisation in Indonesia.DesignA cross-sectional study analysing secondary data from the 2018 Indonesian Basic Health Survey.SettingNational-level survey data from Indonesia.ParticipantsA total of 629 370 participants were included in the study.InterventionWe employed no interventionPrimary and second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…49 Moreover, access to health services is hampered by the unequal distribution of health services in Indonesia, which tends to be more advanced in the western regions. 50 , 51 This is particularly pertinent for the people of eastern Indonesia. On the other hand, this presents an opportunity for western Indonesian health services to develop medical tourism services for eastern Indonesians.…”
Section: Discussionmentioning
confidence: 99%
“…49 Moreover, access to health services is hampered by the unequal distribution of health services in Indonesia, which tends to be more advanced in the western regions. 50 , 51 This is particularly pertinent for the people of eastern Indonesia. On the other hand, this presents an opportunity for western Indonesian health services to develop medical tourism services for eastern Indonesians.…”
Section: Discussionmentioning
confidence: 99%
“…But there are significant variations in hospital utilization among different regions, which could contribute to inaccurate estimates of cancer incidence rates. 46 Vietnam is also confronted with similar issues as Indonesia. Besides economic development and healthcare disparities, the lack of healthcare policies and resources contributes to inaccurate cancer data in Vietnam.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, cancer registration is mainly conducted by hospital‐based cancer registries in Indonesia. But there are significant variations in hospital utilization among different regions, which could contribute to inaccurate estimates of cancer incidence rates 46 . Vietnam is also confronted with similar issues as Indonesia.…”
Section: Discussionmentioning
confidence: 99%
“…The study supports previous studies that reported disparities in the utilization of primary health among regions in rural Indonesia. Regions in western Indonesia tend to have better utilization of Puskesmas in rural areas [ 8 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%